2019
DOI: 10.1055/a-0985-4272
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 Acts Centrally to Induce Sympathetic Activation of Brown Adipose Tissue and Non-Shivering Thermogenesis

Abstract: Nesfatin-1 has originally been established as a bioactive peptide interacting with key hypothalamic nuclei and neural circuitries in control of feeding behavior, while its effect on energy expenditure has only recently been investigated. Hence, the aim of this study was to examine whether centrally acting nesfatin-1 can induce β3-adrenergic stimulation, which is a prerequisite for the activation of thermogenic genes and heat release from interscapular brown adipose tissue, key physiological features that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…The anorexigenic properties of nesfatin-1 were reported for the first time by Oh-I and collaborators [ 2 ]. This seminal finding was confirmed and further extended by other research groups [ 3 5 ] and by us [ 6 , 7 ]. In addition, nesfatin-1 administration into the central nervous system (CNS) was also shown to increase body core temperature [ 8 ] and energy expenditure [ 6 , 7 , 9 ], thereby indicating its major role in the central regulation of energy homeostasis.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The anorexigenic properties of nesfatin-1 were reported for the first time by Oh-I and collaborators [ 2 ]. This seminal finding was confirmed and further extended by other research groups [ 3 5 ] and by us [ 6 , 7 ]. In addition, nesfatin-1 administration into the central nervous system (CNS) was also shown to increase body core temperature [ 8 ] and energy expenditure [ 6 , 7 , 9 ], thereby indicating its major role in the central regulation of energy homeostasis.…”
Section: Introductionsupporting
confidence: 83%
“…This seminal finding was confirmed and further extended by other research groups [ 3 5 ] and by us [ 6 , 7 ]. In addition, nesfatin-1 administration into the central nervous system (CNS) was also shown to increase body core temperature [ 8 ] and energy expenditure [ 6 , 7 , 9 ], thereby indicating its major role in the central regulation of energy homeostasis. In fact, NUCB2 and/or nesfatin-1 (here named NUCB2/nesfatin-1 as common antibodies do not distinguish between NUCB2 and nesfatin-1) is highly expressed in homeostatic centers such as the hypothalamus and brainstem [ 2 , 10 13 ].…”
Section: Introductionsupporting
confidence: 83%
“…We previously showed that nesfatin-1 injected i.c.v. promotes thermogenesis by increasing both iBAT and tail temperature (indices of heat production and dissipation, respectively) 5 39 . In the present study, thermal imaging revealed that iBAT and tail temperature in Nucb2/nesfatin-1 knockdown animals did not differ from controls in baseline condition and thus did not account for the difference in energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the thermogenetic effect of nesfatin-1 mainly depends on b3-adrenergic stimulation. In addition, levels of Dio2 and cell death inducing DFFA like effector A (CIDEA) mRNA were increased in brown adipose tissue after nesfatin-1 administration, which is plausible as both are involved in regulating the thermogenic program (46). Since the direct effects of peripherally injected nesfatin-1 on vascular smooth muscle were attenuated by pretreatment with propranolol, an involvement of the b-adrenergic system can also be suspected here (57).…”
Section: Colocalization With Other Peptidesmentioning
confidence: 99%